Discrepancy evaluation of social reconstruction-based curriculum implementation at Sekolah Rimba Indonesia - Rika Yustikarini (Curricula: Journal of Curriculum Development, 2023)
This study aims to determine the suitability of implementing a social reconstruction-based curriculum at Sekolah Rimba Indonesia based on the ideological criteria and characteristics of the social reconstruction curriculum of experts, namely John D., Mc Neil, and Michael Stephen Schiro used the discrepancy evaluation model. The selected resource persons are teachers and principals at Sekolah Rimba. This data collection technique is through interviews, observations, and document studies. The data analysis technique used Miles and Hubberman, namely condensation and presentation of data, and conclusion. The results of the study describe the implementation of a social reconstruction-based curriculum at Sekolah Rimba Indonesia, which includes aspects of the basic concepts and objectives of the social reconstruction curriculum, teaching perspectives, the nature of learning, teaching, and evaluation have been following the criteria set at the beginning of the study. The implementation of the curriculum at Sekolah Rimba Indonesia can be maintained and used as a reference for schools that adopt the social reconstruction curriculum. In this study, the long-term outcomes assessment aspect of Sekolah Rimba Indonesia was not included as an aspect of the research.